Assessment of social demand for environmental and cultural heritage preservation: evidence from a discrete choice experiment in Tunisia - Missaoui, Sameh; Rahmani, Djamel; Thabet, Chokri; Feás, Jacobo; Gíl, José María; Akaichi, Faical (Frontiers in Environmental Economics, 2023)
Weighing cultural legacies is crucial to better understand the opportunity costs of lagoon restoration. It may be necessary for local populations whose wellbeing and culture are closely linked to heritage. This paper investigates the preferences and willingness to pay (WTP) of local fishermen for contributing to the restoration of the Bizerte lagoon (Tunisia, North Africa) and the management of the Manzel Abderrahmen harbor through the implementation of the EcoPact project. For this purpose, a discrete choice experiment (DCE) survey was conducted in the port with 50 local fishers. The results of this work represent a particular contribution to the literature as they offer a different perspective on the willingness to pay for the benefits of Cultural Bequest. Manzel Abderrahmen fishermen view “port organization” as an economic, cultural, and recreational attribute that drives their choices. The fishermen showed their willingness to accept all the taxes mentioned in the questionnaire and to increase the actual tax (9%) up to 13% over 5 years to complete the design of their port. This suggests that decision-makers should be aware of the omitted legacy values that could influence subsequent decision-making.